Unhappy Cities - Glaeser, Edward L.; Gottlieb, Joshua D.; Ziv, Oren (Journal of Labor Economics, 2016)
There are persistent differences in self-reported subjective well-being across US metropolitan areas, and residents of declining cities appear less happy than others. Yet some people continue to move to these areas, and newer residents appear to be as unhappy as longer-term residents. While historical data on happiness are limited, the available facts suggest that cities that are now declining were also unhappy in their more prosperous past. These facts support the view that individuals do not maximize happiness alone but include it in the utility function along with other arguments. People may trade off happiness against other competing objectives.